Improved drug loading via spray drying of a chalcone implant for local treatment of cutaneous leishmaniasis. (2nd September 2018) - Sousa-Batista, Ariane J.; Arruda-Costa, Natalia; Rossi-Bergmann, Bartira; Ré, Maria Inês
Abstract: Current chemotherapy of cutaneous leishmaniasis (CL), even the mildest forms, encompasses multiple and painful injections with toxic drugs that cause systemic adverse effects. Recently, we showed the promising use of poly(lactic-co-glycolic acid) (PLGA) microparticles loaded with an antileishmanial nitrosylated chalcone (CH8) for effective, safe, local, and single-dose treatment of CL. Here, we proposed to optimize the delivery system by increasing the CH8 loading in PLGA-microparticles using spray drying instead of emulsification-solvent evaporation. The effect of solvent composition and polymeric matrix changes on thermal properties, loading efficiency, particle size, morphology, and spatial drug distribution of the CH8-loaded microparticles was evaluated. The results showed that spray drying allowed a higher CH8 content (18% w/w), as contrasting with the previous solvent evaporation technique that maximally incorporated 7.8% of CH8. In vitro studies on 96-hour incubation with L. amazonensis -infected macrophages showed that entrapment in spray-dried PLGA microparticles rendered CH8 safer, preserved its antileishmanial activity, and did not affect its antioxidant properties.